The Common Cold: A Review of the Literature (International Journal of Food and Nutritional Sciences, 2022)
The most common illness in humans is respiratory viral infections, commonly known as the common cold. Despite their innocuous appearance, they are a leading source of illness and death throughout the globe. Several viruses have been linked to this kind of disease, including The most common is rhinovirus. Symptom generation is the result of a combination of viral cytotoxicity and inflammatory system activation. As a result, antiviral therapy alone may not be enough to avoid severe complications. The most effective use of such drugs necessitates an early start. As a result, developing reliable and quick diagnosis methods for respiratory viruses is critical. Prior to any dependable and efficient. Although therapy is accessible, symptomatic treatments may be the sole option for treatment. All intellectual property rights are retained.